The Effect of Aqueous Extract and Essential Oils of the Leaves of Eucalyptus incrassate on Î²- Lactam Resistant Staphylococcus aureus - Salman, Ehab D.; AL-Saedi, Abbas J. H.; AL-Kazzaz, Amel Gh. M.; Yahya, Suhad S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
According to the extraction procedure , Eucalyptus incrassata leave sample yielded 5% and 2% w/w(Based on dry leaves ) of the aqueous extract and essential oils respectively. Disk diffusion method was used to determine the antimicrobial activity of aqueous extract and essential oils of E . incrassata leaves against eight isolates of multidrug- resistant of Staphylococcus aureus ( S. aureus) . It was found that aqueous extract and essential oils have variable antimicrobial activity(the inhibition zone diameter ranged from 7 to 14 mm respectively ) , while essential oils showed more effect than aqueous extract .         It was noticed that values of Minimal Inhibitory Concentration ( MIC )  for aqueous extract is different from MIC of  essential oils and these values were ranged from12.5 to 75mg/ml . It was also found that isolates collected from wound infections showed high resistance against aqueous extract and essential oils with MIC ranged from 50-75mg/ml, these variation in the MIC are probably due to some virulence factors which have a unique genetic determinant .  The results indicated that the potential usefulness of the aqueous extract and essential oils of Eucalyptus incrassata as an antimicrobial agent can be used in the treatment of multidrugresistant S. aureus infectious .